2013
DOI: 10.4149/neo_2013_031
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role of NF1 in cancer

Abstract: NF1 proteins are a family of transcription factors that act either as repressors or as activators. Functional studies indicate that NF1 participate in signaling pathways that regulate cell viability, proliferation and differentiation. Participation in regulation of genes important for tumor progression and metastasizing suggests a potential value of NF1 as a prognostic factor for certain types of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Ras/MAPK activity can be aberrantly stimulated via the overexpression of RTKs or copy number alterations of KRAS and BRAF . Also, loss of DUSP4 or somatic alterations of NF1 in TNBC can contribute to the activation of RAF/MEK/ERK pathway [ 74 , 75 ]. Preclinical studies have demonstrated that basal type breast cancer cells have an activated RAS-like transcriptional program and are significantly more sensitive to MEK inhibitors compared with luminal and HER-2 amplified lines.…”
Section: Main Textmentioning
confidence: 99%
“…Ras/MAPK activity can be aberrantly stimulated via the overexpression of RTKs or copy number alterations of KRAS and BRAF . Also, loss of DUSP4 or somatic alterations of NF1 in TNBC can contribute to the activation of RAF/MEK/ERK pathway [ 74 , 75 ]. Preclinical studies have demonstrated that basal type breast cancer cells have an activated RAS-like transcriptional program and are significantly more sensitive to MEK inhibitors compared with luminal and HER-2 amplified lines.…”
Section: Main Textmentioning
confidence: 99%
“…In contrast to the highly conserved N-terminal DNA binding domain, the C-terminal region of NFIB, which encodes a transactivation domain, diverges extensively between other NFI members as well as between isoforms, and therefore might promote interactions with different nuclear regulatory proteins depending on the cellular context ( Gronostajski, 2000 ). Adding to this complexity, post-translational modifications (phosphorylation, O- or N-glycosylation) can significantly influence the activity of NFI proteins ( Sabova et al, 2013 ). Fig.…”
Section: Nfib Gene Regulation and Downstream Targetsmentioning
confidence: 99%
“…The protein product of NF1 gene, neurofibromin, is a multifunctional protein involved in many cellular signaling pathways, including RAS/MAPK and mTOR pathways, both of which are dysregulated in many cancer types. 21 CTNNB1, Wnt/b-catenin, is a highly complex pathway and plays a vital role in bone development and homeostasis and is dysregulated in many human malignancies, including bone cancers and, especially, osteosarcomas. 22 Although on a small sample set, we were able to identify a preliminary set of 9 probes (8 gene loci: FAM181B, KANK2, NPR3, PON3, RAB32, RAI1, SLC16A5, and ZNF397OS) that were differentially methylated between control samples and chordomas that recurred and tumors that did not recur.…”
Section: -14mentioning
confidence: 99%